2018
DOI: 10.1029/2018jd028597
|View full text |Cite
|
Sign up to set email alerts
|

Spring Onset Predictability in the North American Multimodel Ensemble

Abstract: The predictability of spring onset is assessed using an index of its interannual variability (the “extended spring index” or SI‐x) and output from the North American Multimodel Ensemble reforecast experiment. The input data to compute SI‐x were treated with a daily joint bias correction approach, and the SI‐x outputs computed from the North American Multimodel Ensemble were postprocessed using an ensemble model output statistic approach—nonhomogeneous Gaussian regression. This ensemble model output statistic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
(47 reference statements)
0
7
0
Order By: Relevance
“…10-m winds from one NMME model, CCSM4, were used to force wave models by Bell and Kirtman (2019). Carrillo et al (2018) find promise in the prediction of the beginning of the spring season using daily maximum and minimum temperature, but only after the application of a sophisticated post-processing. They point out that the length of training period and ensemble size are both important for developing a skillful forecast for spring onset, a common theme amongst studies that use the Phase II database.…”
Section: Emerging and Future Directionsmentioning
confidence: 99%
“…10-m winds from one NMME model, CCSM4, were used to force wave models by Bell and Kirtman (2019). Carrillo et al (2018) find promise in the prediction of the beginning of the spring season using daily maximum and minimum temperature, but only after the application of a sophisticated post-processing. They point out that the length of training period and ensemble size are both important for developing a skillful forecast for spring onset, a common theme amongst studies that use the Phase II database.…”
Section: Emerging and Future Directionsmentioning
confidence: 99%
“…Improvements could be made to the climate forecast integration, such as improved downscaling methods or the addition of alternative global climate models. Carrillo et al (2018) found a large increase in skill by using a post-hoc ensemble bias correction with a long training time series, and a similar bias correction could be applied to in our system. There are other abiotic drivers which are important for phenology, such as precipitation and daylength (Diez et al, 2012).…”
Section: Discussionmentioning
confidence: 75%
“…While several studies have shown ecological forecasting can be aided by weather and climate forecasts (Carrillo et al, 2018;Van Doren and Horton, 2018), climate forecasts with a lead time of 1 year or less are still rarely used in ecology, likely because of the associated computational challenges (Taylor and White, 2020). Our species level analyses show some potential value for incorporating these climate forecasts, which produced increases in skill for two of the most common plants in our forecast system, Forsythia spp.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Demand for information and ecological forecasts at multiple time scales is growing considerably among natural resource managers to guide planning and anticipate change (Bradford et al, ; Dietze et al, ). This information could serve as a valuable complement to seasonal and shorter‐term weather and phenology forecasts (Carillo et al, ; Kirtman et al, ; Mo & Lettenmaier, ; Saha et al, ).…”
Section: Introductionmentioning
confidence: 99%